2000
DOI: 10.1097/00005131-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Comparison of a Distal Femoral Side Plate and a Retrograde Intramedullary Nail

Abstract: The mechanical advantages favor the use of the side plate if fixation stiffness is essential. The axial mode of failure occurs distally for both fixation devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Plates exhibited greater plastic deformation than nails (0.29 vs. 0.76 mm at 2,500 N). These findings are in consistent with a multitude of other biomechanical studies investigating osteosynthesis stiffness and osteosynthesis movement in various fracture models [10,23,41,44]. Using an osteoporotic saw-bone model Wähnert et al [41] investigated four different implants (T2 intramedullary nail, supracondylar nail, distal femoral nail, AxSOS angular plate) under torsional and axial loading conditions.…”
Section: Load In Newton (N) Deformation In Milimeter (Mm)supporting
confidence: 78%
“…Plates exhibited greater plastic deformation than nails (0.29 vs. 0.76 mm at 2,500 N). These findings are in consistent with a multitude of other biomechanical studies investigating osteosynthesis stiffness and osteosynthesis movement in various fracture models [10,23,41,44]. Using an osteoporotic saw-bone model Wähnert et al [41] investigated four different implants (T2 intramedullary nail, supracondylar nail, distal femoral nail, AxSOS angular plate) under torsional and axial loading conditions.…”
Section: Load In Newton (N) Deformation In Milimeter (Mm)supporting
confidence: 78%
“…There is agreement, throughout a range of studies of distal femoral fracture management [9][10][11][27][28][29] , that plating provides greater torsional stiffness, whereas intramedullary devices have greater axial strength. In our study, all intramedullary devices showed similar axial stiffness compared with each other.…”
Section: Discussionmentioning
confidence: 99%
“…[11,[26][27][28][29] Regarding axial stiffness of plate constructs, the literature shows a range from 10% to 25% of axial stiffness achieved with IM nails. [30] Sufficient implant anchorage is a challenge particularly in the treatment of osteoporotic distal femoral fractures.…”
Section: Discussionmentioning
confidence: 99%